Cross-cultural validation and inter-rater reliability of the Personal and Social Performance scale, Thai version - Manit Srisurapanont (2018)
Objective: To cross-culturally validate and examine the inter-rater reliability of the Personal and Social Performance scale (PSP), Thai version (Thai-PSP). Material and Method: The authors translated, back translated, and conducted a panel review on the source, translated, and back translated version of the PSP. After nine psychiatrists, who were new to the PSP or the Thai-PSP, had received a three-hour session of training, they jointly watched four tape-recorded interviews and used the Thai-PSP for independent rating of the patients' functioning. Results: The score ranges for items 1 (socially useful activities), 2 (personal/social relationships), and 3 (selfcare) were between 0 (absent) and 4 (severe). The score range was between 0 (absent) and 3 (marked) for item 4 (disturbing /aggressive behavior). The total scores of four patients were rated between 2 (21-30 points) and 8 (81-90 points). The intraclass correlation coefficients (95% confidence intervals) of each item and total score were as follows: 0.63 (0.28-0.96) for item 1, 0.75 (0.42-0.98) for item 2, 0.69 (0.35-0.97) for item 3, 0.52 (0.17-0.94) for item 4, and 0.75 (0.41-0.98) for the total score. Conclusion: The results of the present study confirm the reliability of PSP and Thai-PSP, as well as the ease of training.